The Effect Of Business Capital And Creativity On Entrepreneurial Interest With The Involvement Of Variables Intervening: Entrepreneurial Motivation On Entrepreneurship Association Of Umkm Muaro Jambi (Asumkmuja) - Rizki Surya Pratama; Dhamiri; Ahmad Nur Budi Utama (Cita konsultindo, 2025)
This study aims to examine the effect of business capital and creativity on entrepreneurial interest by involving entrepreneurial motivation as an intervening variable among members of the Entrepreneurship Association of UMKM Muaro Jambi (ASUMKMUJA). Using a quantitative approach, data were collected through questionnaires distributed to ASUMKMUJA members and analyzed using path analysis. The findings indicate that business capital and creativity have a positive and significant effect on entrepreneurial motivation. Furthermore, entrepreneurial motivation significantly influences entrepreneurial interest and mediates the relationship between business capital, creativity, and entrepreneurial interest. These results suggest that enhancing both financial support and creative capacity, while simultaneously fostering entrepreneurial motivation, can effectively increase entrepreneurial interest among UMKM actors. This study provides useful insights for policymakers and entrepreneurship development programs to support the growth of small and medium enterprises in the region.